Reaction of indoles with aromatic fluoromethyl ketones: an efficient synthesis of trifluoromethyl(indolyl)phenylmethanols using K2CO3/n-Bu4PBr in water - Pillaiyar, Thanigaimalai; Sedaghati, Masoud; Schnakenburg, Gregor (Beilstein Journal of Organic Chemistry, 2020)
A new, mild and efficient protocol for the synthesis of trifluoromethyl(indolyl)phenylmethanols by the reaction of indoles with a variety of aromatic fluoromethyl ketones in the presence of K2CO3 (15 mol %) and n-Bu4PBr (15 mol %) in water. The desired products were obtained in good to excellent yields without requiring a column chromatographic purification. The reusability of the catalytic system and large-scale synthesis of indolyl(phenyl)methanols, which would further transform into biological active indole-derived compounds, are further advantages of this protocol.
Keywords: C–C-bond formation; C3-funtionalization of indole; diindolylmethane; Friedel–Crafts reaction; indole; indole-3-carbinol; large-scale synthesis; recyclability